Effect of gambir extract Uncaria gambierRoxb. on fetal of pregnant mice induced by alcohol - A, Almahdy (INDONESIAN JOURNAL OF PHARMACY, 2010)
Anomaly  in  the  fetus  of  mice  may  induced  by  the  present  of  oxidative stress on the dam during gestation. Alcohol is a potential substance that able to generate the oxidative stress. Antioxidant theoretically should reduce the above process.  Gambir  extract  is  a  notorious  non  toxic  herbal  which  rich  of antioxidants.  This  study  aims  to  see  whether  the  oxidative  stress  in pregnant mice  induced  by  alcohol  could  be  suppressed  with  gambir  extracts.  The results showed that administration of gambir extract to thepregnant dam of mice after been induced by alcohol during gestation, reduced the presence of a thrombus on the pup.Key words: Gambir extract, ethanol, teratogen, mice